Hybrid dual emission in perovskite-coated GaN-based ultraviolet light-emitting diodes - Jeong, Seonghoon; Lee, Yohan; Choi, Yunju; Kim, Hyunsoo (한국물리학회, 2025)
We report on the hybrid dual-emission characteristics of GaN-based ultraviolet light-emitting diodes (UV-LEDs) integrated with CH3NH3PbBr3 (MAPbBr(3)) perovskite photoluminescent coatings. The resulting device exhibits two spectrally distinct emission bands: a near-UV peak arising from the InGaN/GaN multiple quantum wells and a green emission generated via radiative reabsorption and subsequent photoluminescence (PL) within the perovskite layer. Contrary to the conventional down-conversion assumption, the green emission intensity diminishes with increasing injection current, while simultaneously exhibiting a substantial spectral narrowing and a fixed red-shift. Both UV and green bands show wavelength shifts and linewidth evolution that indicate complex light-matter interactions at the GaN/sapphire/perovskite interfaces, including nonlinear photon reabsorption, saturation of excitonic recombination, and cavity-modulated optical filtering. These findings redefine the role of perovskite coatings as more than passive converters and suggest their active photonic influence on emission dynamics in hybrid LED architectures.